Involved-field irradiation or elective-nodal irradiation in neoadjuvant chemo-radiotherapy for locally-advanced esophageal cancer: comprehensive analysis for dosimetry, treatment-related complications, impact on lymphocyte, patterns of failure and survival - Chen, Xianyan; Zhang, Yingjie; Zhou, Xiaojuan; Wang, Min; Na, Feifei; Zhou, Lin; Xu, Yong; Zou, Bingwen; Xue, Jianxin; Liu, Yongmei; Gong, Youling (Frontiers in Oncology, 2023)
Purpose: To compare the differences between involved-field irradiation (IFI) and elective nodal irradiation (ENI) in selecting the optimal target area for neoadjuvant chemoradiotherapy (nCRT) in patients with locally advanced esophageal squamous cell carcinoma (LA-ESCC).We retrospectively analyzed 267 patients with LA-ESCC, of whom 165 underwent ENI and 102 underwent IFI. Dosimetry, treatment-related complications, pathological responses, recurrence/metastasis patterns, and survival were compared between the two groups.The median follow-up duration was 27.9 months. The R0 resection rates in the IFI and ENI groups were 95.1% and 92.7%, respectively (p=0.441), while the pathological complete response (pCR) rates were 42.2% and 34.5%, respectively (p=0.12). The ENI group received higher radiation doses to the heart (HV30:23.9% vs. 18%, p=0.033) and lungs (LV30:7.7% vs. 4.9%, p<0.001) than the IFI group.Consequently, the ENI group showed a higher incidence of grade 2 or higher radiation pneumonitis (30.3% vs. 17.6%, p=0.004) and pericardial effusion (26.7% vs. 11.8%, p=0.021) than the IFI group. Post-operation fistulas were observed in 3(2.9%) and 17 cases (10.3%) in the IFI and ENI groups, respectively (p=0.026). In the multivariate analysis, smoking, positive lymph node involvement (pN+), and anastomotic fistula were independent predictors of overall survival (OS). The pN+ patients exhibited a greater propensity for recurrence compared to pN-patients, especially in the first year of follow-up (6.67% vs. 0.56%, p=0.003).The ENI group had a higher incidence of radiation-induced adverse events compared to the IFI group, likely due to the higher radiation doses to normal tissues. Considering the similar disease-free survival (DFS) and OS rates in the two groups, IFI may be suitable for nCRT in patients with LA-ESCC, although further prospective studies are warranted.